ISLAMIC TEACHERPRENEURSHIP: MENYIAPKAN PENDIDIK MUSLIM YANG BERDAYA SAING GLOBAL - Chasanah, Uswatun; Agustina, Isnaeni; Kurniati, Edy Dwi (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT This article discusses the concept of Islamic Teacherpreneurship as an innovative approach in preparing Muslim educators who have global competitiveness. Islamic Teacherpreneurship is an integration of Islamic values, teacher competencies, and entrepreneurial spirit that is the basis for developing the professionalism of contemporary Muslim educators. This study uses a comprehensive literature study approach by analyzing various scientific publications related to Islamic education, entrepreneurship, and teacher professionalism. The stages of this research include searching for relevant literature, in-depth reading, coding themes related to Islamic Teacherpreneurship, grouping codes into broader categories, analyzing patterns and relationships between categories, and interpreting and synthesizing findings to construct a conceptual framework, with validation through source triangulation. The results of the study indicate that Islamic Teacherpreneurship contributes significantly to character formation, capacity building, and development of learning innovations for Muslim educators. Through the implementation of Islamic Teacherpreneurship, Muslim educators are not only able to transfer Islamic knowledge and values, but also develop leadership skills, creativity, innovation, and economic independence. This study has implications for the urgency of developing an Islamic education curriculum based on entrepreneurship and a continuing professional development program for Muslim educators to improve their competitiveness in the era of globalization and the industrial revolution 4.0 towards society 5.0. ABSTRAK Artikel ini membahas konsep Islamic Teacherpreneurship sebagai pendekatan inovatif dalam menyiapkan pendidik Muslim yang memiliki daya saing global. Islamic Teacherpreneurship merupakan integrasi antara nilai-nilai Islam, kompetensi keguruan, dan jiwa kewirausahaan yang menjadi basis pengembangan profesionalisme pendidik Muslim kontemporer. Penelitian ini menggunakan pendekatan studi literatur komprehensif dengan menganalisis berbagai publikasi ilmiah yang berkaitan dengan pendidikan Islam, entrepreneurship, dan profesionalisme guru. Tahapan penelitian ini meliputi penelusuran literatur relevan, pembacaan mendalam, pengkodean tema terkait Islamic Teacherpreneurship, pengelompokan kode ke dalam kategori, analisis pola dan hubungan antar kategori, serta interpretasi dan sintesis untuk membangun kerangka konseptual, dengan validasi melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa Islamic Teacherpreneurship berkontribusi signifikan dalam pembentukan karakter, peningkatan kapasitas, dan pengembangan inovasi pembelajaran bagi pendidik Muslim. Melalui implementasi Islamic Teacherpreneurship, pendidik Muslim tidak hanya mampu mentransfer pengetahuan dan nilai-nilai keislaman, tetapi juga mengembangkan kemampuan leadership, kreativitas, inovasi, dan kemandirian ekonomi. Penelitian ini berimplikasi pada urgensi pengembangan kurikulum pendidikan Islam berbasis kewirausahaan serta program pengembangan profesional berkelanjutan bagi pendidik Muslim untuk meningkatkan daya saing mereka di era globalisasi dan revolusi industri 4.0 menuju society 5.0.